Zeolite belonging to ZSM-48 family, and method of producing the same

JP2025022008APending Publication Date: 2025-02-14TOSOH CORP

Patent Information

Application Number
JP2023126199
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-02
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0010】 本発明により、安価で取り扱いが容易なNBAをSDAとして使用する、アルミノシリケートであるZSM-48ファミリーに属するゼオライトの製造方法、及びそれにより得られるZSM-48ファミリーに属するゼオライトの少なくともいずれかを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025022008000001_ABST
    Figure 2025022008000001_ABST
Patent Text Reader

Abstract

To provide a method of producing zeolite i.e., aluminosilicate belonging to ZSM-48 family, using low-cost and easily handleable NBA as SDA, and at least one species of zeolite belonging to ZSM-48 family obtained by the method.SOLUTION: There is provided zeolite belonging to ZSM-48 family, i.e., aluminosilicate including normal butylamine in the amount of 0.1 mass% or more and 10 mass% or less and at least having a powder X-ray diffraction peak as shown in the following table 1.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to zeolites belonging to the ZSM-48 family. [Background technology]

[0002] Zeolites belonging to the ZSM-48 family are zeolites having one-dimensional pores with 10-membered oxygen rings. Zeolites belonging to the ZSM-48 family include aluminosilicates whose skeletal structure is made up of aluminum and silicon atoms, and borosilicates whose skeletal structure is made up of boron and silicon atoms. Among them, zeolites belonging to the ZSM-48 family, which are aluminosilicates, are known to show high olefin selectivity as catalysts for the MTO (methanol to olefin) reaction (for example, Patent Document 1).

[0003] Patent Document 2 discloses that dicationic structure directing agents (hereinafter also referred to as "SDAs") such as pentamethonium have high directivity toward zeolites belonging to the ZSM-48 family. Non-Patent Document 1 also studies the synthesis of zeolites belonging to the ZSM-48 family using an inexpensive and small-bulk SDA such as normal butylamine (hereinafter also referred to as "NBA"). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2022 / 063992 [Patent Document 2] U.S. Patent No. 8003074 [Non-patent literature]

[0005] [Non-Patent Document 1] Micropor.Mesopor.Mater.2009, vol.119,pp.259-266 Summary of the Invention [Problem to be solved by the invention]

[0006] Patent Document 2 discloses the use of dicationic SDA such as pentamethonium in the synthesis of zeolites belonging to the ZSM-48 family. However, dicationic SDA is expensive and bulky, and therefore requires calcination at high temperatures to remove the SDA after crystallization. Since high-temperature calcination requires a large amount of energy, there is a demand for zeolites belonging to the ZSM-48 family that use SDA that can be removed with less energy consumption, from the viewpoints of reducing costs and reducing environmental loads.

[0007] In Non-Patent Document 1, SDA, which is inexpensive and has a small bulk like NBA, is used to synthesize zeolites belonging to the ZSM-48 family. However, zeolites belonging to the ZSM-48 family produced using NBA are limited to borosilicates whose framework atoms are composed of boron and silicon. Zeolites belonging to the ZSM-48 family, which are borosilicates, do not have catalytic activity and are unsuitable as catalysts for MTO reactions.

[0008] An object of the present disclosure is to provide a method for producing a zeolite belonging to the ZSM-48 family, which is an aluminosilicate, using NBA, which is inexpensive and easy to handle, as an SDA, and at least one of the zeolites belonging to the ZSM-48 family obtained thereby. [Means for solving the problem]

[0009] The gist of the present invention is as follows, and the gist of the present disclosure is as follows. [1] A zeolite belonging to the ZSM-48 family which contains 0.1% by mass or more and 10% by mass or less of n-butylamine and has at least the following powder X-ray diffraction peaks, and which is an aluminosilicate. [Table 1] [2] The zeolite belonging to the ZSM-48 family according to [1] above, having a molar ratio of silica to alumina of 1,300 or more and 20,000 or less. [3] The zeolite belonging to the ZSM-48 family according to [1] or [2] above, having an average crystal grain size of 0.2 μm or more and 1.5 μm or less. [4] A method for producing a zeolite belonging to the ZSM-48 family according to any one of [1] to [3] above, comprising: a crystallization step of crystallizing a composition containing a silica source, an alumina source, n-butylamine, an alkali source, and water in the presence of seed crystals. Effect of the Invention

[0010] According to the present invention, it is possible to provide at least one of a method for producing a zeolite belonging to the ZSM-48 family, which is an aluminosilicate, using NBA, which is inexpensive and easy to handle, as an SDA, and a zeolite belonging to the ZSM-48 family obtained thereby. [Brief description of the drawings]

[0011] [Figure 1] 1 is a powder X-ray diffraction pattern of the zeolite belonging to the ZSM-48 family in Example 1. [Diagram 2] FIG. 2 is a scanning electron microscope image of the zeolite belonging to the ZSM-48 family in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, the zeolite belonging to the ZSM-48 family of the present disclosure will be described with reference to an example of an embodiment.

[0013] The terms used in this embodiment are as follows.

[0014] An "aluminosilicate" is a composite oxide having a structure consisting of a repeating network of aluminum (Al) and silicon (Si) via oxygen (O). Among aluminosilicates, those that have a crystalline XRD peak in their powder X-ray diffraction (hereinafter also referred to as "XRD") pattern are "crystalline aluminosilicates", and those that do not have a crystalline XRD peak are "amorphous aluminosilicates".

[0015] "Borosilicate" is a composite oxide in which boron (B) has been introduced instead of the aluminum in aluminosilicate.

[0016] In this embodiment, the XRD pattern can be obtained by XRD measurement under the following conditions. Acceleration current / voltage: 40mA / 40kV Radiation source: CuKα radiation (λ=1.5405Å) Measurement mode: Continuous scan Scan condition: 40° / min Measurement range: 2θ=3° to 43° Divergence vertical limit slit: 10mm Divergence / entrance slit: 1° Receiving slit: open Receiving solar slit: 5° Detector: Semiconductor detector (D / teX Ultra) Filter: Ni filter

[0017] The crystalline XRD peak is a peak that is detected by identifying the 2θ of the peak top in the analysis of the XRD pattern using a general analysis software (e.g., SmartLab StudioII, manufactured by Rigaku). The half-width (full width at half maximum) of the crystalline XRD peak can be 2θ=0.50° or less, for example. The following conditions can be used as the analysis conditions for the XRD pattern. Fitting conditions: Automatic, refine background Dispersive pseudo-Voigt function (peak shape) Background removal method: Fitting method Kα2 removal method: Kα1 / Kα2 ratio=0.497 Smoothing method: B-Spline curve Smoothing conditions: second-order differential method, σ cut value = 3, χ threshold = 1.5

[0018] The XRD pattern can be measured using a general powder X-ray diffraction device (eg, Ultima IV Protectus, manufactured by Rigaku).

[0019] "Zeolite" is a compound in which the skeleton atoms (hereinafter also referred to as "T atoms") have a regular structure with oxygen (O) interposed therebetween, and the T atoms are at least one of metal atoms and metalloid atoms. The metal atoms can be exemplified by one or more selected from the group consisting of aluminum (Al), titanium (Ti), iron (Fe), zinc (Zn), gallium (Ga) and tin (Sn). The metalloid atoms can be exemplified by one or more selected from the group consisting of boron (B), silicon (Si), germanium (Ge), arsenic (As), antimony (Sb) and tellurium (Te). Zeolite in which the T atoms are aluminum (Al) and silicon (Si) corresponds to crystalline aluminosilicate.

[0020] A "zeolite-like substance" is a compound having a regular structure in which T atoms are oxygen-mediated, and the T atoms contain at least an atom other than a metal or a metalloid. Examples of zeolite-like substances include complex phosphorus compounds containing phosphorus (P) as the T atom, such as aluminophosphate (AlPO) and silicoaluminophosphate (SAPO). "Zeolite-like substances" are distinguished from "zeolites" in which the T atoms are composed of at least one of a metal atom and a metalloid atom.

[0021] The "ordered structure" of zeolite and zeolite-like substances refers to a skeletal structure specified by the skeletal structure code (hereinafter simply referred to as the "structure code") established by the Structure Commission of the International Zeolite Association (hereinafter also referred to as "IZA"), and a skeletal structure having an intergrowth structure described on the IZA homepage "http: / / www.iza-struture.org / databases / ". For example, "ZSM-48" is a zeolite having a skeletal structure composed of an intergrowth of polymorphs ZSM-48_A and ZSM-48_B.

[0022] In this embodiment, the term "ZSM-48 family" refers to a group of ZSM-48s having different ratios of polymorph ZSM-48_A and polymorph ZSM-48_B (hereinafter also referred to as "intergrowth ratios"), and "belonging to the ZSM-48 family" refers to any ZSM-48 constituting the ZSM-48 family. The term "ZSM-48 family" includes ZSM-48s with any intergrowth ratio, except for those with 0% polymorph ZSM-48_A and those with 0% polymorph ZSM-48_B.

[0023] The framework structure of zeolite (ZSM-48) can be identified by comparison with the XRD pattern (known XRD pattern) of ZSM-48, which constitutes the ZSM-48 family. For example, the XRD pattern of ZSM-48 used for comparison is the XRD pattern (http: / / asia.iza-structure.org / IZA-SC / DO_structures / DO_pow_plot_diffax.php?poly_mix=ZSM-48_A-ZSM-48_B) (hereinafter also referred to as "reference pattern") described in 1-dimensional stacking disorder of Intergrowth on the IZA Structure Committee homepage (http: / / www.iza-struture.org / databases / ).

[0024] The "average crystal grain size" is the average value of the particle sizes of primary particles. A primary particle is the smallest unit of particle that can be observed independently in a scanning electron microscope (hereinafter also referred to as "SEM") observation under the following conditions. The SEM observation may be performed using a general scanning electron microscope (for example, apparatus name: JSM-IT200, manufactured by JEOL Ltd.). Accelerating voltage: 5 kV Magnification: 10,000 ± 5,000 times

[0025] For the "average crystal grain size", first, 100 ± 10 primary particles that can be observed without interruption of the contour in the SEM observation image are arbitrarily extracted, the longest diameter of each of the extracted primary particles is measured, and the average value thereof is obtained, which may be taken as the average crystal diameter. The number of SEM observation images may be any number as long as the number of primary particles can be observed as described above, and one or a plurality of SEM observation images may be used.

[0026] <Zeolite belonging to the ZSM-48 family> Hereinafter, the zeolite belonging to the ZSM-48 family of the present embodiment will be described.

[0027] The zeolite belonging to the ZSM-48 family of the present embodiment contains 0.1% or more and 10% by mass or less of normal butylamine (hereinafter also referred to as "NBA"), has at least the XRD peaks shown in Table 2 below, and is an aluminosilicate.

Table 2

[0028] In the present embodiment, having the XRD peaks shown in the table means that peaks having the relative peak intensities shown in the table can be confirmed in the XRD pattern within the range of the lattice plane spacing d (Å) shown in the table. Further, that a peak can be confirmed within the range of the lattice plane spacing d (Å) shown in the table means that a peak having a peak top within the range of the lattice plane spacing d (Å) can be confirmed.

[0029] The zeolite belonging to the ZSM-48 family of this embodiment may contain XRD peaks with a relative peak intensity of less than 5% in its XRD pattern, and such XRD peaks do not need to be taken into consideration for identifying the framework structure.

[0030] The XRD pattern does not indicate the crystal structure by each independent XRD peak itself, but by a single XRD pattern consisting of a group of XRD peaks having specific relative intensities, the crystal structure of a zeolite belonging to the ZSM-48 family is indicated. A change in the lattice spacing and relative intensity of the XRD peaks means a change in the crystal structure. Therefore, the crystal structure of the zeolite belonging to the ZSM-48 family of this embodiment can be identified by the group of XRD peaks having these relative intensities.

[0031] The zeolite belonging to the ZSM-48 family of this embodiment may have at least the XRD peaks shown in Table 2 in its XRD pattern, and may further include XRD peaks (hereinafter also referred to as "other XRD peaks") other than the XRD peaks shown in Table 2. Among zeolites belonging to the ZSM-48 family of this embodiment that further include such other XRD peaks, the zeolite preferably has the XRD peaks shown in Table 3 below, and more preferably has the XRD peaks shown in Table 4 below.

[0032] [Table 3]

[0033] [Table 4]

[0034] The zeolite belonging to the ZSM-48 family of this embodiment is an aluminosilicate. The zeolite belonging to the ZSM-48 family of this embodiment is an aluminosilicate, which makes it suitable as a catalyst for the MTO (methanol to olefin) reaction. If the zeolite belonging to the ZSM-48 family is a zeolite other than an aluminosilicate such as a borosilicate, it does not have catalytic activity and is difficult to use as a catalyst for the MTO reaction.

[0035] The zeolite belonging to the ZSM-48 family of this embodiment contains normal butylamine (NBA) in an amount of 0.1 mass% or more and 10 mass% or less. Here, the mass ratio of NBA in the zeolite belonging to the ZSM-48 family of this embodiment (hereinafter also referred to as "NBA content") is the ratio relative to 100 mass% of the zeolite belonging to the ZSM-48 family containing NBA.

[0036] The lower limit of the NBA content may be 0.1% by mass or more, but is preferably 2% by mass or more, and more preferably 3% by mass or more, since it is more likely to have the preferred XRD peaks shown in Tables 3 and 4. The upper limit of the NBA content may be 10% by mass or less, but is preferably 9% by mass or less, and more preferably 8% by mass or less, since excess NBA is less likely to exist outside the framework of the zeolite belonging to the ZSM-48 family. The combination of the upper and lower limits of the NBA content described above is arbitrary, but the preferred range of the NBA content in the zeolite belonging to the ZSM-48 family of this embodiment is 2% by mass or more and 9% by mass or less, and the particularly preferred range of the NBA content is 3% by mass or more and 8% by mass or less.

[0037] In this embodiment, the NBA content can be obtained by dividing the mass of NBA contained in the zeolite belonging to the ZSM-48 family by the mass of the zeolite belonging to the ZSM-48 family (the zeolite belonging to the ZSM-48 family containing NBA) and converting the result into a percentage. The mass of NBA contained in the zeolite belonging to the ZSM-48 family can be measured by the change in mass when the zeolite belonging to the ZSM-48 family (the zeolite belonging to the ZSM-48 family containing NBA) is heated from 120°C to 500°C. The change in mass when the zeolite belonging to the ZSM-48 family is heated can be measured under the following conditions using a general differential thermogravimetric analyzer (e.g., STA 2500 Regulus, manufactured by NETZSCH). Atmosphere: Air Atmospheric flow rate: 20cc / min Heating rate: 10℃ / min Measurement temperature: 20~800℃

[0038] In addition, the mass change (mass loss) of zeolite belonging to the ZSM-48 family up to 120°C can be determined to be a mass change resulting from the desorption of adsorbed water, and the mass change (mass loss) of zeolite belonging to the ZSM-48 family above 500°C can be determined to be a mass change resulting from the condensation of silanols at the junction surfaces of the polymorphic zeolite belonging to the ZSM-48 family. Therefore, the mass change (mass loss) of zeolite belonging to the ZSM-48 family when heated from 120°C to 500°C can be determined to be a mass change resulting from the combustion of NBA.

[0039] The molar ratio of silica to alumina in the zeolite belonging to the ZSM-48 family of this embodiment (hereinafter also referred to as "SiO2 / Al2O3 ratio") is preferably 1300 or more, or 1400 or more, and is preferably 20000 or less, 10000 or less, or 5000 or less, because a highly crystalline zeolite belonging to the ZSM-48 family with reduced impurities can be obtained. The upper and lower limits of the SiO2 / Al2O3 ratio in the zeolite belonging to the ZSM-48 family of this embodiment may be any combination of the above-mentioned upper and lower limits. The specific range of the SiO2 / Al2O3 ratio in the zeolite belonging to the ZSM-48 family of this embodiment is preferably 1300 or more and 20000 or less, more preferably 1300 or more and 10000 or less, and even more preferably 1400 or more and 5000 or less.

[0040] The average crystal grain size of the zeolite belonging to the ZSM-48 family of this embodiment is preferably 0.2 μm or more, and preferably 1.5 μm or less, 1.3 μm or less, or 1.0 μm or less, because when the zeolite belonging to the ZSM-48 family is subjected to an MTO reaction, coking (carbon adhesion) is suppressed and the catalyst can have a long life. The combination of the upper and lower limits of the average crystal grain size described above is arbitrary, but the range of the average crystal grain size of the zeolite belonging to the ZSM-48 family of this embodiment is preferably 0.2 μm or more and 1.5 μm or less, more preferably 0.2 μm or more and 1.3 μm or less, and even more preferably 0.2 μm or more and 1.0 μm or less.

[0041] The zeolite belonging to the ZSM-48 family of this embodiment may contain an alkali metal. Examples of the alkali metal include one or more selected from the group consisting of lithium (Li), sodium (Na), potassium (K), rubidium (Rb) and cesium (Cs), and further examples include at least one of sodium (Na) and potassium (K), and further examples include sodium (Na).

[0042] In the zeolite belonging to the ZSM-48 family of this embodiment, the content of the alkali metal can be, for example, 0 mass% or more, more than 0 mass%, or 0.05 mass% or more, and can be, for example, 1 mass% or less, 0.5 mass% or less, or 0.3 mass% or less, relative to 100 mass% of the zeolite belonging to the ZSM-48 family including NBA. The combination of the upper and lower limits of the alkali metal content described above is arbitrary, but the range of the alkali metal content in the zeolite belonging to the ZSM-48 family of this embodiment can be, for example, 0 mass% or more and 1 mass% or less, more than 0 mass% and 0.5 mass% or less, or 0.05 mass% or more and 0.3 mass% or less. In this specification, a content of 0 mass% means that the substance is not contained.

[0043] The molar ratio of the total amount of alkali metals to aluminum in the zeolite belonging to the ZSM-48 family of this embodiment (hereinafter also referred to as "M / Al ratio", where "M" is the total molar amount of alkali metals contained in the zeolite belonging to the ZSM-48 family) can be, for example, 0.2 or more, or 0.5 or more, and can be, for example, 6 or less, or 4 or less. The combination of the upper and lower limits of the M / Al ratio described above is arbitrary, but the range of the M / Al ratio in the zeolite belonging to the ZSM-48 family of this embodiment can be 0.2 or more and 6 or less, and preferably 0.5 or more and 4 or less.

[0044] The content of silanol groups in the zeolite belonging to the ZSM-48 family of this embodiment (hereinafter also referred to as "silanol amount") is preferably 0.05 mmol / g or more, 0.10 mmol / g or more, 0.50 mmol / g or more, or 1.00 mmol / g or more, and is preferably 2.0 mmol / g or less, 1.90 mmol / g or less, or 1.80 mmol / g or less, from the viewpoint of being more easily applicable as a catalyst for MTO reaction. The combination of the upper and lower limits of the silanol amount described above is arbitrary, but the range of the silanol amount in the zeolite belonging to the ZSM-48 family of this embodiment is preferably 0.05 mmol / g or more and 2.0 mmol / g or less, more preferably 0.10 mmol / g or more and 1.90 mmol / g or less, even more preferably 0.50 mmol / g or more and 1.90 mmol / g or less, and particularly preferably 1.00 mmol / g or more and 1.80 mmol / g or less.

[0045] In this embodiment, the "silanol group" refers to a skeleton end formed by bonding silicon (Si) of the T atom with a hydroxyl group (OH). Therefore, the amount of silanol is affected by the amount of silicon in the skeleton structure. For example, a zeolite with a larger amount of silicon in the skeleton structure, i.e., a zeolite with a higher SiO2 / Al2O3 ratio, tends to have more silanol groups. In general, when the amount of silanol is large, the skeleton structure is more likely to collapse in a high-temperature atmosphere. In contrast, when the amount of silanol is the above value, the zeolite belonging to the ZSM-48 family of this embodiment is expected to have high durability and is more easily applicable as a catalyst for the MTO reaction.

[0046] The amount of silanol in zeolites belonging to the ZSM-48 family is 1 It can be determined from the H MAS NMR spectrum. Specifically, a zeolite belonging to the ZSM-48 family that has been evacuated to a vacuum is 1 H MAS NMR was measured and the obtained 1The amount of silanol in a zeolite belonging to the ZSM-48 family can be determined by determining the integrated intensity of the proton peak (the peak having a peak top in the range of 2.0 ± 0.5 ppm) assigned to a silanol group from the H MAS NMR spectrum and applying this to a calibration curve showing the relationship between integrated intensity and proton amount to identify the corresponding proton amount.

[0047] Zeolites belonging to the ZSM-48 family 1 For H MAS NMR measurements, a zeolite belonging to the ZSM-48 family can be used that has been evacuated at room temperature, then collected and weighed under a nitrogen atmosphere. The calibration curve used to determine the amount of silanol is based on the results of a test for a substance with a known amount of protons (e.g., benzene). 1 1H MAS NMR measurement is performed and the obtained 1 It can be obtained by determining the integrated intensity of the proton peak (peak having a peak top in the range of 2.0 ± 0.5 ppm) assigned to the silanol group from the H MAS NMR spectrum, and creating a line (calibration curve) showing the relationship between the amount of protons and the integrated intensity.

[0048] The area intensity of the proton peak assigned to the silanol group is 1 The area (integral value) of the separated peaks can be obtained by separating the peaks of the protons assigned to the silanol groups from the H MAS NMR spectrum and determining the area (integral value) of the separated peaks. A conventionally known peak separation method (peak fitting) can be used to separate the peaks, and for example, the least squares method assuming a function representing the peaks can be used. Examples of the function representing the peaks include the Gaussian function, the Lorentz function, a mixed function of the Gaussian distribution and the Lorentz distribution (Gauss-Lorentz), and the Voigt function. Peak separation by the least squares method may be performed using standard NMR data processing software (software name: ALICE2, JEOL). In addition, 1 The spectrum measured by 1 H MAS NMR spectroscopy may be subjected to background correction before peak separation. For the background correction, for example, the Shirley method can be used.

[0049] In this embodiment, 1 The 1 H MAS NMR spectrum measurement can be carried out using a general solid-state nuclear magnetic resonance apparatus (for example, VNMRS-400, manufactured by Varian). 1 The measurement conditions for the H MAS NMR spectrum can be, for example, the following conditions. 1 H resonance frequency: 399.8MHz Rotor speed: 15kHz Repeat time: 10 seconds Number of times: 32

[0050] The zeolite belonging to the ZSM-48 family of this embodiment can be used as a catalyst for the MTO reaction as it is, but can also be used as a catalyst for the MTO reaction after removing SDA. Therefore, from the viewpoint of making the zeolite belonging to the ZSM-48 family of this embodiment more applicable as a catalyst for the MTO reaction, the zeolite belonging to the ZSM-48 family of this embodiment is preferably a zeolite belonging to the ZSM-48 family in which the amount of silanol measured after performing the SDA removal treatment and the ion exchange treatment under the following conditions is 0.05 mmol / g or more, 0.10 mmol / g or more, or 0.15 mmol / g or more, and more preferably a zeolite belonging to the ZSM-48 family in which the amount of silanol is 1.0 mmol / g or less, 0.90 mmol / g or less, or 0.80 mmol / g or less. [SDA removal processing conditions] A zeolite belonging to the ZSM-48 family is calcined at 600° C. for 2 hours in an air atmosphere. [Ion exchange treatment conditions] The fired product obtained by the SDA removal treatment is brought into contact with an aqueous solution containing ammonium chloride in an amount 0.5 times the mass of the fired product at 80°C ± 5°C for 1 minute, and then the fired product is washed with pure water in an amount 1,000 times the mass of the fired product, dried in an air atmosphere at 110°C for 18 hours, and fired in an air atmosphere at 550°C for 1 hour.

[0051] The upper and lower limits of the silanol amount measured after the SDA removal treatment and the ion exchange treatment may be combined in any combination, but the range of the silanol amount measured after the SDA removal treatment and the ion exchange treatment is preferably 0.05 mmol / g or more and 1.0 mmol / g or less, more preferably 0.10 mmol / g or more and 0.90 mmol / g or less, and even more preferably 0.15 mmol / g or more and 0.80 mmol / g or less.

[0052] In the zeolite belonging to the ZSM-48 family of this embodiment, the molar ratio of silanol groups to silicon (hereinafter also referred to as the "SiOH / Si ratio") is 1.0 × 10 -2 or more, or 1.5 x 10 -2 For example, 6.0×10 -2 or less than 5.0 x 10 -2 The above-mentioned upper and lower limits of the SiOH / Si ratio may be arbitrarily combined, but from the viewpoint of making the catalyst more applicable to the MTO reaction, the SiOH / Si ratio is preferably in the range of 1.0×10 -2 Above 5.0×10 -2 It is preferable that:

[0053] The SiOH / Si ratio is 1The above-mentioned amount of silanol obtained from the 29Si MAS NMR spectrum can be determined by dividing it by the amount of silicon in the zeolite belonging to the ZSM-48 family. The amount of silicon in the zeolite belonging to the ZSM-48 family of the present embodiment can be determined by inductively coupled plasma (hereinafter also referred to as "ICP") emission spectroscopic analysis. As a method for measuring the amount of silicon by ICP emission spectroscopic analysis, a measurement method by a calibration curve method can be mentioned. The calibration curve used in the calibration curve method is created by measuring the intensity of the emission peak corresponding to silicon (Si) (the intensity at the peak top) for a standard solution with a known amount of silicon and drawing a line (calibration curve) showing the relationship between the intensity and the amount of silicon. By measuring the intensity of the ICP emission peak (the intensity at the peak top) of the zeolite belonging to the ZSM-48 family, which is the measurement sample, and applying it to the calibration curve showing the relationship between the intensity and the silicon content to specify the corresponding amount of silicon, the amount of silicon in the zeolite belonging to the ZSM-48 family can be determined. In addition, a general ICP emission spectroscopic analyzer (for example, apparatus name: OPTIMA3300DV, manufactured by PERKIN ELMER) can be used for ICP emission spectroscopic analysis.

[0054] <Method for producing zeolite belonging to ZSM-48 family> Hereinafter, the method for producing the zeolite belonging to the ZSM-48 family of the present embodiment will be described.

[0055] The method for producing the zeolite belonging to the ZSM-48 family of the present embodiment is a production method including a crystallization step of crystallizing a composition containing a silica source, an alumina source, NBA, an alkali source, and water (hereinafter also referred to as "raw material composition") in the presence of a seed crystal. Thereby, the zeolite belonging to the ZSM-48 family of the present embodiment can be obtained.

[0056] The silica source contained in the raw material composition is silica (SiO2) or a compound containing silicon that serves as a precursor thereof, and examples thereof include one or more selected from the group consisting of colloidal silica, amorphous silica, sodium silicate, tetraethyl orthosilicate, precipitated silica, fumed silica, crystalline aluminosilicate, and amorphous aluminosilicate. One or more selected from the group consisting of colloidal silica, tetraethyl orthosilicate, crystalline aluminosilicate, amorphous aluminosilicate, and sodium silicate is preferred, at least one of colloidal silica and amorphous aluminosilicate is more preferred, and amorphous aluminosilicate is even more preferred.

[0057] The alumina source contained in the raw material composition is a compound containing alumina (Al2O3) or aluminum that serves as a precursor thereof, and examples thereof include one or more selected from the group consisting of aluminum sulfate, sodium aluminate, aluminum hydroxide, aluminum hydroxide gel, aluminum chloride, amorphous aluminosilicate, crystalline aluminosilicate, and metallic aluminum. The alumina source is preferably one or more selected from the group consisting of sodium aluminate, aluminum hydroxide, aluminum sulfate, crystalline aluminosilicate, and amorphous aluminosilicate, more preferably at least one of sodium aluminate and amorphous aluminosilicate, and even more preferably amorphous aluminosilicate.

[0058] Among the above-mentioned alumina sources and silica sources, particularly preferred alumina sources and silica sources are amorphous aluminosilicates.

[0059] The SiO2 / Al2O3 ratio in the raw material composition (for example, the SiO2 / Al2O3 ratio of amorphous aluminosilicate) is preferably 1200 or more, 1300 or more, or 1400 or more, and is preferably 20000 or less, 15000 or less, or 10000 or less, since this makes it easier to produce zeolite belonging to the ZSM-48 family, which is an aluminosilicate. The combination of the upper and lower limits of the SiO2 / Al2O3 ratio described above is arbitrary, but the range of the SiO2 / Al2O3 ratio in the raw material composition (for example, the SiO2 / Al2O3 ratio of amorphous aluminosilicate) is preferably 1200 or more and 20000 or less, more preferably 1300 or more and 15000 or less, and even more preferably 1400 or more and 10000 or less.

[0060] In addition, when a starting material other than the alumina source contained in the raw material composition contains aluminum, it can be regarded as the alumina source. For example, when the silica source is a substance containing aluminum, such as a crystalline aluminosilicate or an amorphous aluminosilicate, the silica source can be simultaneously regarded as the alumina source. As a specific silica source containing aluminum, for example, an amorphous aluminosilicate having an aluminum content (hereinafter also referred to as "aluminum content") calculated as Al2O3 relative to 100 mass% of the silica source can be exemplified.

[0061] The raw material composition contains NBA. NBA is an SDA directed to zeolites belonging to the ZSM-48 family, and zeolites belonging to the ZSM-48 family can be obtained by using this. Zeolites crystallized using SDA usually contain SDA in their pores, but NBA, which is small in bulk, can be removed not only by calcination treatment but also by acid treatment, and therefore can be removed from zeolites belonging to the ZSM-48 family with less energy consumption than dicationic SDAs (bulky SDAs) such as pentamethonium, which are difficult to remove by acid treatment.

[0062] The raw material composition may contain an SDA source directed to a zeolite belonging to the ZSM-48 family other than NBA, but from the viewpoint of further suppressing the energy consumption required for the SDA removal treatment, it is preferable that the raw material composition does not contain a dication-based SDA source such as bulky pentamethonium. Examples of SDA sources other than NBA directed to a zeolite belonging to the ZSM-48 family include one or more amines selected from the group consisting of ethylenediamine, di-n-butylamine, n-propylamine, di-n-propylamine, dipropylenetriamine, triethylenetetramine, diethylenetriamine, ethanolamine, and propanolamine, tetramethylammonium, glycerol, alcohols, and morpholine, and these can be used alone or in combination.

[0063] The molar ratio of silica to SDA in the raw material composition (hereinafter also referred to as "SDA / SiO2 ratio") can be 0.01 or more, or 0.03 or more, and can be 1.0 or less, 0.35 or less, or 0.25 or less. The combination of the upper and lower limits of the SDA / SiO2 ratio described above is arbitrary, but the range of the SDA / SiO2 ratio in the raw material composition can be 0.01 or more and 1.0 or less, 0.01 or more and 0.35 or less, or 0.03 or more and 0.25 or less. In addition, SDA in the SDA / SiO2 ratio means the total amount of SDA including NBA.

[0064] The alkali source may be a compound containing an alkali metal element, and may be at least one of an alkali metal hydroxide and an alkali metal halide. The alkali metal is preferably at least one selected from the group consisting of lithium, sodium, potassium, rubidium, and cesium, more preferably at least one of sodium and potassium, and even more preferably sodium.

[0065] The molar ratio of silica to alkali metal in the raw material composition (hereinafter also referred to as "M / SiO2 ratio") is preferably 0.05 or more, 0.08 or more, or 0.10 or more, and preferably 1.0 or less, 0.60 or less, or 0.30 or less, because this makes it easier to produce zeolite belonging to the ZSM-48 family, which is an aluminosilicate. The combination of the upper and lower limits of the M / SiO2 ratio described above is arbitrary, but the range of the M / SiO2 ratio in the raw material composition is preferably 0.05 or more and 1.0 or less, more preferably 0.08 or more and 0.60 or less, and even more preferably 0.10 or more and 0.30 or less. Note that M in the M / SiO2 ratio is the total amount of alkali metal, and when the alkali metal is sodium, or when the alkali metal is sodium and potassium, M / SiO2 is Na / SiO2 or (Na+K) / SiO2, respectively.

[0066] The molar ratio of silica to hydroxide ions in the raw material composition (hereinafter also referred to as "OH / SiO2 ratio") is preferably 0.05 or more, 0.08 or more, or 0.10 or more, and preferably 1.0 or less, 0.80 or less, or 0.60 or less, because this makes it easier to produce zeolite belonging to the ZSM-48 family, which is an aluminosilicate. The combination of the upper and lower limits of the OH / SiO2 ratio described above is arbitrary, but the range of the OH / SiO2 ratio in the raw material composition is preferably 0.05 or more and 1.0 or less, more preferably 0.08 or more and 0.80 or less, and even more preferably 0.10 or more and 0.60 or less.

[0067] The water may be at least one selected from the group consisting of distilled water, deionized water, and pure water. Furthermore, moisture derived from other starting materials contained in the raw material composition, such as solvents and water-containing compounds, can also be considered as water in the raw material composition.

[0068] The molar ratio of silica to water in the raw material composition (hereinafter also referred to as "H2O / SiO2 ratio") can be, for example, 5 or more, 7 or more, or 9 or more, and can be, for example, 80 or less, 50 or less, or 30 or less. The combination of the upper and lower limits of the above-mentioned H2O / SiO2 ratio is arbitrary, but the range of the H2O / SiO2 ratio in the raw material composition can be, for example, 5 or more and 80 or less, 7 or more and 50 or less, or 9 or more and 30 or less.

[0069] In the production method of this embodiment, the raw material composition preferably has any combination of the molar compositions shown below, since this makes it easier to produce a zeolite belonging to the ZSM-48 family, which is an aluminosilicate. SiO2 / Al2O3 ratio: 1200 or more, 1300 or more, or 1400 or more, and 20,000 or less, 15,000 or less, or 10,000 or less SDA / SiO2 ratio: 0.01 or more or 0.03 or more, and 1.0 or less, 0.35 or less, or 0.25 or less M / SiO2 ratio: 0.05 or more, 0.08 or more, or 0.10 or more, and 1.0 or less, 0.60 or less, or 0.30 or less OH / SiO2 ratio: 0.05 or more, 0.08 or more, or 0.10 or more, and 1.0 or less, 0.80 or less, or 0.60 or less H2O / SiO2 ratio: 5 or more, 7 or more, or 9 or more, and 80 or less, 50 or less, or 30 or less

[0070] In the crystallization step, the raw material composition is crystallized in the presence of seed crystals. As a method for crystallizing the raw material composition in the presence of seed crystals, a method of crystallizing a mixture obtained by mixing the raw material composition with seed crystals can be exemplified. The amount of seed crystals used for crystallization (hereinafter also referred to as "seed crystal amount") can be exemplified as a mass ratio of silicon in the seed crystals converted into silica to the mass (100 mass%) of silicon in the raw material composition (not including seed crystals) converted into silica (SiO2), and can be exemplified as more than 0 mass% or 0.5 mass% or more, and can be exemplified as 10 mass% or less, 5 mass% or less, or 3.5 mass% or less. The combination of the upper and lower limits of the above-mentioned seed crystal amount is arbitrary, but the range of the seed crystal amount can be exemplified as a mass ratio of silicon in the seed crystals converted into silica to the mass (100 mass%) of silicon in the raw material composition (not including seed crystals) converted into silica (SiO2), and can be exemplified as more than 0 mass% to 10 mass% or less, more than 0 mass% to 5 mass% or less, or 0.5 mass% to 3.5 mass% or less.

[0071] The seed crystals may be any zeolite having a microstructure in its crystal structure common to zeolites belonging to the ZSM-48 family. For example, the seed crystals are preferably one or more zeolites having any of the skeletal structures selected from the group consisting of zeolites belonging to the ZSM-48 family, AFI type, MFI type, MEL type, MWW type, YFI type, IMF type, and CON type, more preferably one or more zeolites having any of the skeletal structures selected from the group consisting of zeolites belonging to the ZSM-48 family, MFI type, MEL type, and MWW type, and even more preferably zeolites belonging to the ZSM-48 family.

[0072] The SiO2 / Al2O3 ratio of the seed crystals is preferably 200 or more, 500 or more, or 1000 or more, and is preferably 100,000 or less, 10,000 or less, or 5,000 or less, since this makes it easier to produce zeolites belonging to the ZSM-48 family, which are aluminosilicates. The upper and lower limits of the SiO2 / Al2O3 ratio of the seed crystals may be combined in any combination, but the range of the SiO2 / Al2O3 ratio of the seed crystals is preferably 200 or more and 100,000 or less, more preferably 500 or more and 10,000 or less, and even more preferably 1,000 or more and 5,000 or less.

[0073] In the manufacturing method of this embodiment, in the crystallization step, the raw material composition is crystallized in the presence of seed crystals. The crystallization may be performed by subjecting the raw material composition to hydrothermal treatment in the presence of seed crystals. The hydrothermal treatment may be performed, for example, by placing the raw material composition and the seed crystals in a sealed pressure-resistant container and heating the container. The hydrothermal treatment conditions may include any combination of the following conditions. Treatment temperature: 80°C or higher or 130°C or higher, and 190°C or lower or 170°C or lower Processing time: 2 to 500 hours Processing pressure: Natural pressure

[0074] The state of the raw material composition in the crystallization step is arbitrary, and may be either still or under stirring, but is preferably under stirring.

[0075] The method for producing a zeolite belonging to the ZSM-48 family of this embodiment may include a post-treatment step such as a washing step or a drying step in addition to the above-mentioned crystallization step.

[0076] In the washing step, the zeolite belonging to the ZSM-48 family obtained by crystallization is washed. Any method for washing may be used, but an example of the washing method is contacting the zeolite belonging to the ZSM-48 family with a sufficient amount of pure water.

[0077] In the drying step, moisture is removed from the crystallized zeolite belonging to the ZSM-48 family or the washed zeolite belonging to the ZSM-48 family. Any drying method can be used, and an example of such a method is drying by heating. In addition, any drying conditions can be used, and an example of such a condition is treating the zeolite in the air at 100° C. or higher and 150° C. or lower for 2 hours to 24 hours.

[0078] The above-mentioned production method can produce the zeolite belonging to the ZSM-48 family of this embodiment. The zeolite belonging to the ZSM-48 family of this embodiment produced by the above-mentioned production method contains NBA as SDA, but NBA is smaller in bulk than dication-based SDA such as pentamethonium, and can be removed not only by calcination treatment but also by acid treatment. Therefore, the zeolite belonging to the ZSM-48 family of this embodiment produced by the above-mentioned production method can remove SDA from the zeolite belonging to the ZSM-48 family with less energy consumption than the zeolite belonging to the ZSM-48 family produced by using a dication-based SDA that is difficult to remove by acid treatment. In addition, since NBA is cheaper than a dication-based SDA, the zeolite belonging to the ZSM-48 family of this embodiment produced by the above-mentioned production method is cheaper than the zeolite belonging to the ZSM-48 family produced by using a dication-based SDA, and is easy to use industrially.

[0079] The zeolite belonging to the ZSM-48 family of this embodiment described above is an aluminosilicate, and therefore can be used as a catalyst for the MTO reaction to produce olefins from methanol. When the zeolite belonging to the ZSM-48 family of this embodiment is used as a catalyst for the MTO reaction, the zeolite belonging to the ZSM-48 family of this embodiment may be brought into contact with methanol. The contact conditions between the zeolite belonging to the ZSM-48 family of this embodiment and methanol are not particularly limited, and conventionally known conditions can be used.

[0080] The zeolite belonging to the ZSM-48 family of this embodiment may be used as it is as a catalyst for the MTO reaction, but may be used as a catalyst for the MTO reaction after being subjected to at least one pretreatment of an SDA removal treatment or an ammonium exchange treatment.

[0081] The SDA removal treatment is a treatment for removing SDA (SDA including NBA) contained in the zeolite belonging to the ZSM-48 family of this embodiment. Examples of the method for the SDA removal treatment include a method for removing SDA by heat treatment and a method for removing SDA by acid treatment. The heat treatment conditions for removing SDA are arbitrary, but an example of the upper limit is treatment in air at 500°C to 700°C for 1 hour to 2 hours. The acid treatment conditions for removing SDA are also arbitrary, but an example of the upper limit is treatment with 20% to 35% hydrochloric acid at a temperature of 110°C to 180°C for 12 hours to 48 hours. From the viewpoint of suppressing fuel consumption for obtaining high temperature conditions, it is preferable to use an acid treatment for removing SDA.

[0082] The ammonium exchange process removes alkali metals from the ZSM-48 family zeolite from which SDA has been removed, and converts the cation type to the ammonium type (hereinafter referred to as "NH4 + The ammonium exchange treatment is a treatment to convert the zeolite into a "ZSM-48 type" zeolite. An example of the ammonium exchange treatment method is a method in which an aqueous solution containing ammonium ions is brought into contact with a zeolite belonging to the ZSM-48 family. The longer the time for which the aqueous solution containing ammonium ions is brought into contact with the zeolite belonging to the ZSM-48 family, the greater the amount of alkali metals removed from the zeolite, and the higher the ammonium ion concentration in the aqueous solution brought into contact with the zeolite belonging to the ZSM-48 family, the greater the amount of alkali metals removed from the zeolite. The conditions for the ammonium exchange treatment may be appropriately adjusted taking such characteristics into consideration. The NH4 obtained by the ammonium exchange treatment is + The zeolite of the cation type was heat-treated to change to the proton type (hereinafter referred to as "H+ Specific heat treatment conditions for converting a cation type zeolite into a proton type zeolite include, for example, in air at 500° C. to 600° C. for 1 hour to 2 hours. EXAMPLES

[0083] Next, examples of the present embodiment will be described, but the present embodiment is not limited to these.

[0084] (Powder X-ray diffraction) The XRD of the sample was measured using a general X-ray diffraction device (device name: UltimaIV Protectus, manufactured by Rigaku) ​​under the following measurement conditions. Acceleration current / voltage: 40mA / 40kV Radiation source: CuKα radiation (λ=1.5405Å) Measurement mode: Continuous scan Scan condition: 40° / min Measurement range: 2θ=3° to 43° Divergence vertical limit slit: 10mm Divergence / entrance slit: 1° Receiving slit: open Receiving solar slit: 5° Detector: Semiconductor detector (D / teX Ultra) Filter: Ni filter

[0085] The XRD patterns obtained as a result of the sample measurements were analyzed using a general analysis software (SmartLab Studio II, Rigaku) ​​under the following conditions to identify the XRD peaks. In addition, the skeletal structure of the sample was identified by comparing the XRD pattern with a reference pattern. Fitting conditions: Automatic, refine background Dispersive pseudo-Voigt function (peak shape) Background removal method: Fitting method Kα2 removal method: Kα1 / Kα2 ratio=0.497 Smoothing method: B-Spline curve Smoothing conditions: second-order differential method, σ cut value = 3, χ threshold = 1.5

[0086] (Composition analysis, quantitative determination of silicon, aluminum, and sodium) The composition of the samples was analyzed using a general inductively coupled plasma optical emission analyzer (instrument name: OPTIMA3300DV, manufactured by PERKIN ELMER). The sample was dissolved in a mixed solution of hydrofluoric acid and nitric acid to prepare a measurement solution. The obtained measurement solution was put into the instrument to analyze the composition of the sample, and each component was quantified using the calibration curve method. The calibration curve was created by measuring the intensity of the emission peak corresponding to the component for a standard solution whose component amount was known, and drawing a line (calibration curve) showing the relationship between the intensity and the amount of the component. The Na / Al ratio and SiO2 / Al2O3 ratio were calculated from the obtained molar concentrations of silicon (Si), aluminum (Al), and sodium.

[0087] (Quantitative determination of NBA content) A typical differential thermogravimetric analyzer (STA 2500 Regulus, manufactured by NETZSCH) was used to quantify the organic components in the samples under the following conditions: The samples were placed in an alumina pan and the weight loss from room temperature to 800°C was analyzed, and the weight loss from 120°C to 500°C was taken as the NBA content. Atmosphere: Air Atmospheric flow rate: 20cc / min Heating rate: 10℃ / min Measurement temperature: 20~800℃

[0088] (Measurement of average crystal grain size) Using a general scanning electron microscope (instrument name: JSM-IT200, manufactured by JEOL Ltd.), the measurement sample was observed under the following conditions. 100±10 primary particles whose outlines were observed without interruption in the obtained SEM observation image were randomly selected, the longest diameter of each selected primary particle was measured, and the average value was calculated, which was taken as the average crystal diameter. Acceleration voltage: 5kV Magnification: 10,000±5,000x

[0089] ( 1 H MAS NMR measurement) A general solid-state nuclear magnetic resonance spectrometer (VNMRS-400, Varian) was used to measure the 1 H MAS NMR spectrum was measured under the following conditions. The measurement sample was dehydrated by holding it at 350-400°C for 5±2 hours under vacuum evacuation, and then collected and weighed under a nitrogen atmosphere. 1 H resonance frequency: 399.8MHz Rotor speed: 15kHz Repeat time: 10 seconds Number of times: 32

[0090] Obtained 1 For the H MAS NMR spectrum, background correction was performed by the Shirley method, and the proton peaks assigned to silanol groups (peaks with peak tops in the range of 2.0 ± 0.5 ppm) were separated. Peak separation (peak fitting) was performed by the least squares method using a mixed function of Gaussian and Lorentzian distributions, using standard NMR data processing software (software name: ALICE2, JEOL). Area integration was performed on the peaks obtained by peak fitting to determine the area intensity, which was then applied to a calibration curve showing the relationship between area intensity and proton amount to determine the amount of silanol. The calibration curve was generated under the above-mentioned conditions for benzene, whose proton amount is known. 1 1H MAS NMR measurement is performed and the obtained 1 The area intensity of the proton peak (peak having a peak top in the range of 2.0 ± 0.5 ppm) assigned to the silanol group was obtained from the H MAS NMR spectrum, and a line (calibration curve) showing the relationship between the amount of protons derived from silanol and the area intensity was prepared.

[0091] (Synthesis of zeolites belonging to the ZSM-48 family) Example 1 Amorphous aluminosilicate (SiO2 / Al2O3 ratio = 3842), NBA, 48 mass% sodium hydroxide, and water were mixed to obtain a raw material composition having the following molar composition. SiO2 / Al2O3 ratio = 3842 NBA / SiO2 ratio = 0.100 Na / SiO2 ratio = 0.129 OH / SiO2 ratio = 0.129 H2O / SiO2 ratio = 11

[0092] The seed crystals (zeolite belonging to the ZSM-48 family, SiO2 / Al2O3 ratio = 2606) were mixed with the raw material composition so that the seed crystal amount (the mass ratio of silicon in the seed crystal converted to silica (SiO2) relative to 100 mass% of silicon in the raw material composition) was 1.1 mass%, and then the raw material composition was filled into an 80 mL sealed container and sealed, and the container was rotated at 55 rpm and hydrothermally treated at 150 ° C for 36 hours at autogenous pressure to obtain a crystallized product. The obtained crystallized product was separated into solid and liquid, washed with pure water, and then dried overnight at 110 ° C in the air to obtain a product, which was the product of this example.

[0093] The product of this example was a zeolite belonging to the ZSM-48 family containing no impurity phases and having the following XRD peaks, and was an aluminosilicate with an NBA content of 4.6 mass%, a SiO2 / Al2O3 ratio of 1460, a Na / Al ratio of 2.79, a silanol content of 1.72 mmol / g, and an average crystal grain size of 0.71 μm. The XRD pattern of the zeolite belonging to the ZSM-48 family of this example is shown in Figure 1, and the scanning electron microscope image is shown in Figure 2. [Table 5]

[0094] Comparative Example 1 A raw material composition having the following molar composition was obtained under the same conditions as in Example 1, except that tetraethyl orthosilicate was used as the silica source (no alumina source was used) instead of the amorphous aluminosilicate (silica source and alumina source) used in Example 1. A product of this comparative example was obtained in the same manner as in Example 1, except that the obtained raw material composition was used instead of the raw material composition used in Example 1, and the raw material composition was subjected to hydrothermal treatment for 72 hours. SiO2 / Al2O3=∞(Al2O3 not included) NBA / SiO2= 0.100 Na / SiO2= 0.129 OH / SiO2= 0.129 H2O / SiO2= 11

[0095] The product of this comparative example was a mixed phase of magadiite and amorphous.

[0096] Comparative Example 2 A raw material composition having the following molar composition was obtained under the same conditions as in Example 1, except that hexamethonium dichloride was used instead of NBA used in Example 1. The product of this comparative example was obtained in the same manner as in Example 1, except that the raw material composition obtained was used instead of the raw material composition used in Example 1, and the raw material composition was subjected to hydrothermal treatment at 180° C. for 24 hours. SiO2 / Al2O3= 3842 SDA / SiO2= 0.200 Na / SiO2= 0.129 OH / SiO2= 0.129 H2O / SiO2= 11

[0097] The product of this comparative example was a zeolite belonging to the ZSM-48 family containing no impurity phases, having the following XRD peaks: NBA content of 0 mass%, hexamethonium dichloride content of 7.8 mass%, SiO2 / Al2O3 ratio of 2606, Na / Al ratio of 15.70, and an aluminosilicate with an average crystal grain size of 0.11 μm. [Table 6]

[0098] [SDA Removal by Acid Treatment (Zeolite Belonging to the ZSM-48 Family in Example 1)] 1 g of the zeolite belonging to the ZSM-48 family obtained in Example 1 and 30 mL of 30 mass % hydrochloric acid were packed in a 100 mL sealed container with a Teflon (registered trademark) inner cylinder, and the container was rotated at 55 rpm and treated at 120°C for 24 hours to perform an acid treatment. Solid-liquid separation was performed to separate the zeolite belonging to the ZSM-48 family from the hydrochloric acid. The separated zeolite belonging to the ZSM-48 family was washed with pure water and then dried overnight at 110°C in the air to obtain an acid-treated zeolite belonging to the ZSM-48 family (hereinafter referred to as "acid-treated zeolite belonging to the ZSM-48 family of Example 1").

[0099] The acid-treated zeolite belonging to the ZSM-48 family of Example 1 had an NBA content of 0.8 mass%, and it was confirmed that SDA (NBA) was removed by the acid treatment. In addition, it was confirmed from the XRD pattern that the acid-treated zeolite belonging to the ZSM-48 family of Example 1 was a zeolite belonging to the ZSM-48 family that did not contain impure phases. It was confirmed that the acid-treated zeolite belonging to the ZSM-48 family of Example 1 had a SiO2 / Al2O3 ratio of 1859, a Na / Al ratio of 0.32, and an average crystal grain size of 0.71 μm.

[0100] [SDA Removal by Heat Treatment (Zeolite Belonging to the ZSM-48 Family in Example 1)] The zeolite belonging to the ZSM-48 family obtained in Example 1 was calcined in an air atmosphere at 600°C for 2 hours to obtain a calcined body (before ion exchange). Then, an aqueous solution in which 0.5 g of ammonium chloride was dissolved per 1 g of the calcined body (before ion exchange) was contacted at 80°C ± 5°C for 1 minute, and the calcined body was washed with 1000 times the mass of pure water, and then dried overnight (18 hours) in an air atmosphere at 110°C. This was calcined in an air atmosphere at 550°C for 1 hour to obtain a calcined body of the zeolite belonging to the ZSM-48 family (hereinafter also referred to as "heat-treated zeolite belonging to the ZSM-48 family of Example 1").

[0101] The heat-treated zeolite belonging to the ZSM-48 family of Example 1 had an NBA content of 0 mass%, and it was confirmed that SDA (NBA) was removed by the heat treatment. In addition, it was confirmed from the XRD pattern that the heat-treated zeolite belonging to the ZSM-48 family of Example 1 was a zeolite belonging to the ZSM-48 family that did not contain impure phases. The heat-treated zeolite belonging to the ZSM-48 family of Example 1 had a SiO2 / Al2O3 ratio of 1792, a Na / Al ratio of 0.39, an average crystal grain size of 0.71 μm, a silanol amount of 0.45 mmol / g, and a SiOH / Si ratio of 2.8 × 10 -2 It was.

[0102] [SDA Removal by Acid Treatment (Zeolite Belonging to the ZSM-48 Family in Comparative Example 2)] An acid-treated zeolite belonging to the ZSM-48 family (hereinafter also referred to as "acid-treated zeolite belonging to the ZSM-48 family of Comparative Example 2") was obtained in the same manner as the above-mentioned acid treatment performed on the zeolite belonging to the ZSM-48 family of Example 1, except that the zeolite belonging to the ZSM-48 family obtained in Comparative Example 2 was used.

[0103] The acid-treated zeolite belonging to the ZSM-48 family of Comparative Example 2 had an NBA content of 0 mass% and a hexamethonium dichloride content of 6.0%. The XRD pattern of the acid-treated zeolite belonging to the ZSM-48 family of Comparative Example 2 confirmed that the zeolite was a zeolite belonging to the ZSM-48 family that did not contain impure phases. The acid-treated zeolite belonging to the ZSM-48 family of Comparative Example 2 had a SiO2 / Al2O3 ratio of 2744, a Na / Al ratio of 3.28, and an average crystal grain size of 0.11 μm. The acid-treated zeolite belonging to the ZSM-48 family of Comparative Example 2 did not have the XRD peaks shown in Table 2.

[0104] [SDA Removal by Heat Treatment (Zeolite Belonging to the ZSM-48 Family in Comparative Example 2)] A calcined body of zeolite belonging to the ZSM-48 family (hereinafter also referred to as "heat-treated zeolite belonging to the ZSM-48 family of Comparative Example 2") was obtained in the same manner as the above-mentioned heat treatment performed on the zeolite belonging to the ZSM-48 family of Example 1, except that the zeolite belonging to the ZSM-48 family obtained in Comparative Example 2 was used.

[0105] The heat-treated zeolite belonging to the ZSM-48 family of Comparative Example 2 had an NBA content of 0% by mass and a hexamethonium dichloride content of 0% by mass. In addition, it was confirmed from the XRD pattern that the heat-treated zeolite belonging to the ZSM-48 family of Comparative Example 2 was a zeolite belonging to the ZSM-48 family that did not contain impure phases. The heat-treated zeolite belonging to the ZSM-48 family of Comparative Example 2 had a SiO2 / Al2O3 ratio of 2606, a Na / Al ratio of 15.70, and an average crystal grain size of 0.11 μm. In addition, the heat-treated zeolite belonging to the ZSM-48 family of Comparative Example 2 did not have the XRD peaks shown in Table 2.

Claims

1. The zeolite belongs to the ZSM-48 family and is an aluminosilicate, containing n-butylamine in an amount of 0.1% by mass or more and 10% by mass or less and having at least the following powder X-ray diffraction peaks: 【Table 1】

2. 2. The zeolite according to claim 1, wherein the molar ratio of silica to alumina is 1,300 or more and 20,000 or less.

3. The zeolite belonging to the ZSM-48 family according to claim 1, having an average crystal grain size of 0.2 μm or more and 1.5 μm or less.

4. 4. A method for producing a zeolite belonging to the ZSM-48 family according to claim 1, comprising: a crystallization step of crystallizing a composition comprising a silica source, an alumina source, n-butylamine, an alkali source, and water in the presence of seed crystals.

Citation Information

Patent Citations

  • Synthesis of high activity ZSM-48

    US8003074B2

  • Methanol to olefin (MTO) process

    WO2022063992A1

Cited By

  • Zeolite belonging to the ZSM-48 family, method for producing the same, and catalyst for MTO reaction

    JP7930519B1